A practicum report conducted at the Brackishwater Aquaculture Center (BAC) - Bayot, Ma. Rhodora N.; Esquivel, Ma. Theresa; Pacoli, Mario (Diliman, Quezon City College of Fisheries, University of the Philippines, 1978)
To meet the increasing demand for fish protein and to offset the nationwide depletion of marine resources from pollution, it is very necessary that aquaculture production should be accelerated. This could be done either by expanding both the coastal and inland areas such as more than 0.5 million hectares of idle swamplands and mangrove areas, or by increasing the yield of the unit areas already cultivated through modern techniques and research. Moreover, to boost inland fishing, training of fishpond owners should also be accelerated. In spite of the fact that our people have engaged in fish farming for quite a time, there is a slow phase in the development of the industry. This may be due to the lack of knowledge on the factors affecting fish production. It is, therefore, with great concern for the future of our aquaculture, that we, the practicum students at the Brackishwater Aquaculture in Leganes, Iloilo studied the situation. This report does not provide all the answers to the nagging problems but practical suggestion are given to improve fish culture in our country.
Report (Undergraduate. Bachelor of Science in Inland Fisheries ) College of Fisheries, University of the Philippines System, 1978.
Keywords: Aquaculture